Disappearances in Mexico From the 'Dirty War' to the 'War on Drugs' - Mandolessi, Silvana; Olalde Rico, Katia (Europa Country Perspectives, 2022)
This volume presents an interdisciplinary analysis of the practice of disappearances in Mexico, from the period of the so-called 'dirty war' to the current crisis of disappearances associated with the country's 'war on drugs', during which more than 80,000 people have disappeared. The volume brings together contributions by distinguished scholars from Mexico, Argentina and Europe, who focus their chapters on four broad axes of enquiry. In Part I, chapters examine the phenomenon of disappearances in its historical and present-day forms, and the struggles for memory around the disappeared in Mexico with reference to Argentina. Part II addresses the political dimensions of disappearances, focusing on the specificities that this practice acquires in the context of the counterinsurgency struggle of the 1970s and the so-called 'war on drugs'. The third section situates the issue within the framework of human rights law by examining the conceptual and legal aspects of disappearances. The final chapters explore the social movement of the relatives of the disappeared, showing how their search for disappeared loved ones involves bodily and affective experiences as well as knowledge production. The volume thus aims to further our understanding of the crisis of disappearances in Mexico without, however, losing sight of the historic origins of the phenomenon.